Nutritional Support for Small Ruminant Development Based on Oil Palm By-products - simon petrus ginting; K Simanihuruk; A Tarigan; K R Pond (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Biomass by-products or plant residues from the plantation system would play a crucial role in animal production since the utilization of forages from the underneath tree crops would be less or minimal when the palm oil crop mature. By-products generated from the palm oil system vary, but in relation to the animal production they could be generally categorized into the fibrous by-products and the non-fibrous (concentrate) by-products. Palm oil mill effluent (POME) and palm kernel cake (PKC) are concentrate by-products produced during the processing of palm oil extraction which have great potency to support sheep and goat production, although limiting factors such as contamination of shell and high copper level in PKC need to be considered in their utilization as feed. The fibrous palm oil by-products include oil palm fronds (OPF) and oil palm trunk (OPT) generated from the palm crop trees and oil palm empty fruit bunch (OPEFB) and palm pressed fiber (PPF) generated from processing of fresh fruits to yield crude oil. These fibrous by-products cannot meet the metabolisable energy required for high growth rate and for lactation of sheep and goats due to low DM digestibility, low crude protein content, low fermentable carbohydrate and low level of intake. Limited inclusion level in ration should be applied for those by-products to yield an acceptable production level of sheep and goats. Pretreatments (physical, chemical, and biological) gave some improvement in their nutritional qualities, however additional cost of pretreatments need to be considered. In the future, there would be a great challenge for the utilization of those fibrous by-products as animal feed since bioconversion of lignocellulosic materials to products such as chemicals (bioethanol, sugar, and bioplastic), fuels, and organic fertilizers are receiving greater interest. Some comparative advantages of these natural wastes are their relatively low cost, renewable and widespread in nature for used in an industrial operation.